1999
DOI: 10.2105/ajph.89.5.747
|View full text |Cite
|
Sign up to set email alerts
|

Preventing weight gain in adults: the pound of prevention study.

Abstract: Obesity has attracted increasing concern in recent years as a public health issue because it is causally related to a variety of negative health outcomes, including diabetes, ' hypertension,2 cardiovascular disease,3 and some cancers,4 and its prevalence in the United States has risen dramatically in the last decade.5 The magnitude of the problem of obesity is further underscored by the fact that extensive research has not yet produced practical and effective long-term treatments for the disorder once it ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
173
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(181 citation statements)
references
References 19 publications
7
173
1
Order By: Relevance
“…In other studies, the activity advice was not clearly reported (12,13,16) . Three studies reported no significant difference in physical activity between groups (13)(14)(15) . One reported no change in fitness but a change in self-reported physical activity (12) .…”
Section: Physical Activitymentioning
confidence: 97%
“…In other studies, the activity advice was not clearly reported (12,13,16) . Three studies reported no significant difference in physical activity between groups (13)(14)(15) . One reported no change in fitness but a change in self-reported physical activity (12) .…”
Section: Physical Activitymentioning
confidence: 97%
“…The majority of the studies in Table 2 were observational, but the Pound of Prevention Study tested an intervention to promote weight maintenance. The primary paper from that study 53 examined weight change as a continuous variable, and therefore was not included in our table. However, two follow-up articles from this same study categorized weight change using different criteria: a 5.0 pound absolute weight change 40 and a 5.0% weight change.…”
Section: Precedents Set In Published Researchmentioning
confidence: 99%
“…These have been described elsewhere in detail, 6 and since this report is not concerned with the effects of the intervention, they are described only brie¯y here. Half of the subjects were assigned to a no-contact control group, one-quarter received education through monthly newsletters, and one-quarter received education plus participation incentives.…”
Section: Subjectsmentioning
confidence: 99%
“…The effects of that intervention on weight-related behaviours and mean change in body weight have been reported previously. 6 The present study describes the prevalence, distribution and correlates of successful weight loss and successful weight maintenance over 3 y. This study is unique in providing data from a non-clinical sample in which success at weight control has been objectively assessed.…”
Section: Introductionmentioning
confidence: 99%